2011
DOI: 10.1016/s1474-4422(11)70188-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive glucose lowering on brain structure and function in people with type 2 diabetes (ACCORD MIND): a randomised open-label substudy

Abstract: Background Persons with type 2 diabetes (T2D) are at risk for cognitive impairment and brain atrophy. The ACCORD Memory in Diabetes (MIND) Study investigated whether persons randomized to an intensive glycaemic therapeutic strategy targeting HbA1c to <6% had better cognitive function and a larger brain volume at 40 months than persons randomized to a standard strategy targeting HbA1c to 7%–7.9%. Methods ACCORD MIND was a double 2×2 factorial parallel group randomised trial conducted in 52 clinical sites in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
367
4
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 486 publications
(394 citation statements)
references
References 36 publications
14
367
4
9
Order By: Relevance
“…To account for a 15% loss to follow-up, .350 participants were recruited for each cell. Power calculations for arriving at these estimates were previously published (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…To account for a 15% loss to follow-up, .350 participants were recruited for each cell. Power calculations for arriving at these estimates were previously published (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…In this context it is important to mention the Action to Control Cardiovascular Risk in Diabetes-Memory In Diabetes (ACCORD-MIND) study, which showed that after 40 months, the rate of brain atrophy on MRI was reduced in patients with type 2 diabetes receiving intensive glycemic control compared with those receiving standard therapy (50). Unfortunately, this positive effect on brain structure was not accompanied by improved cognitive functioning.…”
Section: Implications and Future Perspectivesmentioning
confidence: 99%
“…DM is a chronic disease, characterized by hyperglycemia, resulting from defects in insulin secretion, insulin action, or both [2,3]. The effects of this disease are being strongly associated with neurophysiological, neurochemical, and behavioral modifications in brain of patients that are also observed in animal model of DM [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%